THE ROLE OF INFORMATION PRIVACY IN CRISIS MANAGEMENT AN ANALYTICAL STUDY OF THE OPINIONS OF THE TEACHING STAFF IN THE TECHNICAL COLLEGE / AL-MUSAYYIB - Sanaa J. Kadhim; Khariya abed fadel; Asmaa Abdul Wahid Malik; Saif Ali Al- Mofraje (Scholar Express Journals, 2022)
The issue of information privacy and crisis management in recent decades has received prominent attention by most researchers, That is, the goal of the current study lies in diagnosing the relationship between information privacy and crisis management, by identifying the role played by (information privacy) as one-dimensional, in improving the effectiveness of dealing with crisis management by its dimensions (pre-crisis stage, crisis As for the second main hypothesis (there is an impact of the privacy of informatics in crisis management), and therefore in order to diagnose this relationship, the opinions of 170 teachers of the Technical College - Al-Musayyab were surveyed, and (153) were recovered, valid for analysis, at a rate of (90%), while the forgetfulness of the questionnaires that were not valid for analysis was (10%), Use SPSS.V24,a set of statistical methods were adopted, such as the arithmetic mean, standard deviation, correlation coefficient Person, regression coefficient, deviation coefficient R2 and Cronbach's alpha coefficient to test the validity of the study's hypotheses stage, post stage). The study determined the first main hypothesis, which is that there is a statistically significant correlation between the privacy of informatics and crisis management, The results were summarized to the existence of a correlation and a statistically significant effect of the privacy of informatics in crisis management to indicate the enjoyment of the teaching staff of the Technical College - Al-Musayyib, which improves Al-Qarah on dealing with crises in order to ensure the development and balance between the privacy of informatics and the skills of dealing with crises among the teachers of the Technical College - Al-Musayyib.
Keywords: information privacy; crisis management; forgetfulness; dimensions